2017
DOI: 10.1097/olq.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Promote Sexual Health in America: A New Vision for Public Health Action

Abstract: Sexual health is considered to be a state of wellness with physical, emotional, mental, and social dimensions. Sexual health can contribute to our overall well-being in each of these dimensions. However, despite the intrinsic importance and positive aspects of sexuality in our lives, the United States presently faces significant challenges related to the sexual health of its citizens, including human immunodeficiency virus, other sexually transmitted infections, viral hepatitis, unintended pregnancies, sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Sexist attitudes are a risk factor and legitimize female violence in romantic relationships (Juarros-Basterretxea et al, 2019). Based on evidence demonstrating the predictive role of sexism and its different sexual violence (Durán & Rodríguez-Domínguez, 2019;Rollero & Tartaglia, 2018) and sexual health (Ford et al, 2017) forms, we propose conducting more future research to identify the possible predictor role about sexual health and sexual violence of SDS adherence types in sexual freedom and sexual shyness areas. To date, only the relation between man-favorable typology and sexual aggression/victimization has been studied.…”
Section: Article In Pressmentioning
confidence: 99%
“…Sexist attitudes are a risk factor and legitimize female violence in romantic relationships (Juarros-Basterretxea et al, 2019). Based on evidence demonstrating the predictive role of sexism and its different sexual violence (Durán & Rodríguez-Domínguez, 2019;Rollero & Tartaglia, 2018) and sexual health (Ford et al, 2017) forms, we propose conducting more future research to identify the possible predictor role about sexual health and sexual violence of SDS adherence types in sexual freedom and sexual shyness areas. To date, only the relation between man-favorable typology and sexual aggression/victimization has been studied.…”
Section: Article In Pressmentioning
confidence: 99%
“…All the sexual health interventions for Black women focused on HIV/STI prevention. Although HIV/STI prevention is necessary to reduce the sexual health disparities that Black women face, including more holistic and asset-based approaches to sexual health, including sexual functioning, sexual satisfaction, and relationship satisfaction (Fortenberry, 2013;World Health Organization, 2006) could be useful in both reducing adverse health outcomes and promoting healthy sexuality (Dailey, 1997;Ford et al, 2017;Kirby, 2008). Studies have shown that incorporating positive aspects such as sexual pleasure promotion, intimacy, sexual desire, and sexual communication can increase contraceptive use and effectiveness (Anderson, 2013).…”
Section: Holistic Sexual Healthmentioning
confidence: 99%
“…For example, as the authors point out, efforts to risk behavior reduction in young women are likely to fail unless they also acknowledge how poverty and mental health, as well as minority-based stressors, exacerbate individual women's participation in risk behaviors. Conceptualizing STI within a syndemic framework represents one example of what the next generation of an evidence-based, youthcentered prevention framework should look like [24]. Leaving no adolescent or young person in our community behind means that we continually identify the underlying inequities that impede their sexual well-being, and we design inclusive solutions that promote their dignity, their choice, their agency, and their equity [5].…”
mentioning
confidence: 99%